Unfinished business : screening the Italian Mafia in the new millennium - Renga, Dana, 1971- (Toronto [Ontario] : University of Toronto Press, 2013)
"Unfinished Business is the first book to examine Italian mafia cinema of the past decade. It provides insightful analyses of popular films that sensationalize violence, scapegoat women, or repress the homosexuality of male protagonists. Dana Renga examines these works through the lens of gender and trauma theory to show how the films engage with the process of mourning and healing mafia-related trauma in Italy
Unfinished Business argues that trauma that has yet to be worked through on the national level is displaced onto the characters in the films under consideration. In a mafia context, female characters are sacrificed and non-normative sexual identities are suppressed in order to solidify traditional modes of viewer identification and to assure narrative closure, all so that the image of the nation is left unblemished."--Pub. desc
Introduction: Trauma, gender, and recent Italian Mafia cinema -- Oedipal conflicts in Marco Tullio Giordana's I cento passi -- Honour, shame and vendetta: Pasquale Scimeca's Placido Rizzotto -- Mafia women in a man's world: Roberta Torre's Angela -- The Mafia noir: Paolo Sorrentino's Le conseguenze dell'amore -- Men of honour, man of glass: Stefano Incerti's L'uomo di vetro -- The female mob boss: Edoardo Winspeare's Galantuomini -- Melancholia and the mob weepie: Davide Barletti and Lorenzo Conte's Fine pena mai: Paradiso perduto -- Mourining disavowed: Matteo Garrone's Gomorra -- Recasting Rita Atria in Marco Amenta's La siciliana ribelle -- Trauma postponed: Claudio Cupellini's Una vita tranquilla -- Epilogue: Why must Caesar die?
Includes bibliographical references (pages 223-243) and index.
JSTOR
Keywords: Gangster films -- Italy -- History and criticism; Mafia in motion pictures; Psychic trauma in motion pictures; Motion pictures and women; Gangster films -- Italy; Films de gangsters -- Italie -- Histoire et critique; Mafia au cinéma.; Traumatisme psychique au cinéma.; Cinéma et femmes; Films de gangsters -- Italie; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Gangster films; Mafia in motion pictures; Motion pictures and women; Psychic trauma in motion pictures; Italy; Mafia; Film; Italien; Criticism, interpretation, etc